Influence of Cavity Size on the Survival of Single Surface Atraumatic Restorative Treatment Using Glass Ionomer Cement with or without Chlorhexidine Diacetate—A Randomized Trial - Roshan Noor Mohamed (MDPI AG, 2021)
The purpose of the present study was to assess the influence of cavity size on the survival of conventional and CHX modified GIC in single surface primary molars receiving Atraumatic Restorative Treatment (ART). A randomized controlled trial with a split-mouth design was conducted on 90 children with symmetrical bilateral single surface carious lesions on primary molars. The teeth were randomly allotted to the conventional GIC group (group 1, n = 90) and CHX modified GIC group (group 2, n = 90). Both groups received atraumatic restorative treatment under rubber dam isolation. The cavity size was measured in terms of depth, mesiodistal, and buccolingual dimensions. The survival of ART restorations was measured after 6, 12, 18, and 24 months. The difference in proportion was tested using the Kruskal–Wallis H test, and survival curve estimation was carried out using the Kaplan–Meier method. The overall survival of all ART restorations was 83.3% at 24 months for the total sample. The survival of conventional GIC at 24 months was 83.9%, and for CHX-modified GIC was 82.7% (p > 0.05). The collective overall success of 65.1% was seen in the cavity volume category of 10–29.9 mm3. CHX modified GIC showed high survival percentage (60%) with depth >3 mm. To conclude, no significant difference was observed in the overall survival percentage of conventional and CHX modified GIC. Survival percentage was highest for cavities with a volume of 10–19.9 mm3.